2014
DOI: 10.1073/pnas.1316911111
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal four-dimensional mapping of subcortical anatomy in human development

Abstract: Growing access to large-scale longitudinal structural neuroimaging data has fundamentally altered our understanding of cortical development en route to human adulthood, with consequences for basic science, medicine, and public policy. In striking contrast, basic anatomical development of subcortical structures such as the striatum, pallidum, and thalamus has remained poorly describeddespite these evolutionarily ancient structures being both intimate working partners of the cortical sheet and critical to divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
302
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 297 publications
(326 citation statements)
references
References 77 publications
23
302
0
1
Order By: Relevance
“…In our sample, the striatum, pallidum, and thalamus, like cortical GM, follow an inverted U-shaped developmental trajectory (Raznahan et al, 2014). Striatum and thalamus volumes peak later than cortical volumes and show a relative delay in males.…”
Section: Subcorticalmentioning
confidence: 62%
“…In our sample, the striatum, pallidum, and thalamus, like cortical GM, follow an inverted U-shaped developmental trajectory (Raznahan et al, 2014). Striatum and thalamus volumes peak later than cortical volumes and show a relative delay in males.…”
Section: Subcorticalmentioning
confidence: 62%
“…The prefrontal and subcortical circuitry implicated in adult fear learning undergoes substantial developmental change from childhood through adulthood (Gogtay et al, 2004;Lenroot and Giedd, 2006;Raznahan et al, 2014). Mirroring these pronounced changes in the brain, numerous studies to date suggest that fear learning and regulation exhibit qualitative changes across development (Figure 1).…”
Section: Developmental Changes In Fear-learning Circuitsmentioning
confidence: 99%
“…In contrast to the development of sensory and motor systems, structural and functional changes within affective neural circuits continue well into young adulthood. The neurocircuitry supporting affective learning and regulation comprises a network of cortical and subcortical regions that exhibit extended maturational trajectories (Gogtay et al, 2004;Raznahan et al, 2014). Variation in early-life experience can persistently alter the development and function of these circuits (Lupien et al, 2009), highlighting the important role of experience-dependent plasticity in determining adult affective outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Box 3: developmental structural neuroimaging Our first major longitudinal insight into the dynamics of in vivo human brain development came from a structural neuroimaging study 157 , which revealed that the maturational trajectory of human gray matter volume follows a curvilinear "inverted-U", rather than showing a linear progression to adult values. Since this seminal study there has been a steep climb in the number of large-scale longitudinal structural neuroimaging datasets 158 and associated research reports detailing the spatiotemporal heterogeneity of neuroanatomical maturation within the brain 16,159 , and charting how the dynamics of structural brain development can vary as a function of genetic 160 , environmental 19 , demographic (e.g. biological sex 159 ), cognitive 161 and clinical 162 factors.…”
Section: Box 2: Population Neurosciencementioning
confidence: 99%
“…It has become clear that these diverse metrics follow distinct developmental trajectories in health 163 , which reflect non-overlapping sets of genetic and environmental influences 18 , but can be inter-related in a spatiotemporally specific manner 164 . These normative observations carry major consequences for the optimal design of structural neuroimaging analysis in clinical populations, because conclusions regarding the presence and regional distribution of cortical abnormalities in a given genetic disorder can vary greatly across different morphometric features 159 .…”
Section: Box 2: Population Neurosciencementioning
confidence: 99%